2020
DOI: 10.1002/edm2.178
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin, ALT and family history as critical markers for the development of type 2 diabetes in obese Japanese children

Abstract: The incidence of overweight and obese children has been increasing worldwide over the past several decades. 1-3 Additionally, health problems caused by obesity, such as type 2 diabetes mellitus (T2D) and metabolic syndrome (MS), have become a serious problem. 1,2 In Japanese children, the incidence of obesity tripled between the 1970s and around 2000, although a tendency towards a slight

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
6
3
Order By: Relevance
“…The association of obesity and low adiponectin level suggested the possibility of adiponectin acting as a biomarker for metabolic syndrome, especially among perimenopausal and postmenopausal women or the elderly [78,79]. Low adiponectin levels were found in obese children with diabetes [80], and a polymorphism of the adiponectin gene resulting in a low adiponectin level was associated with diabetes [81]. Homeostatic model assessment (HOMA) including adiponectin level showed better prediction for metabolic syndrome than HOMA insulin resistance itself [82].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…The association of obesity and low adiponectin level suggested the possibility of adiponectin acting as a biomarker for metabolic syndrome, especially among perimenopausal and postmenopausal women or the elderly [78,79]. Low adiponectin levels were found in obese children with diabetes [80], and a polymorphism of the adiponectin gene resulting in a low adiponectin level was associated with diabetes [81]. Homeostatic model assessment (HOMA) including adiponectin level showed better prediction for metabolic syndrome than HOMA insulin resistance itself [82].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Studies in children on the possible association between liver-function enzymes and obesity-related diseases, such as metabolic syndrome and NAFLD, are limited but indicate the significant relationship between the activity of ALT and MetS components [ 13 , 14 ]. In obese Japanese children with MetS or type 2 diabetes (T2DM), ALT showed a very good discriminatory power for the onset of T2DM [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in children on the possible association between liver-function enzymes and obesity-related diseases, such as metabolic syndrome and NAFLD, are limited but indicate the significant relationship between the activity of ALT and MetS components [ 13 , 14 ]. In obese Japanese children with MetS or type 2 diabetes (T2DM), ALT showed a very good discriminatory power for the onset of T2DM [ 14 ]. Another recent large European multicenter cross-sectional study which assessed the prevalence of prediabetes and T2DM in obese children, with varying degrees of elevated transaminases, showed much higher risk of prediabetes and T2DM if the increase in ALT activity was up to two-fold the upper reference limit [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are inconsistent with those of previous studies. 9 , 25 Nielsen et al observed 756,219 individuals and found a 1 μg/mL low plasma adiponectin was associated with an increased risk of T2D. 9 Yasuda et al identified 107 obese children and found plasma adiponectin levels in T2D group are significantly lower than those of the metabolic syndrome and healthy groups.…”
Section: Discussionmentioning
confidence: 99%